The Effect of Applications to Polyphonic Solfege Terms Based on Cooperative Learning Method - Sager, Turan; Gurpinar, Engin; Zahal, Onur (HACETTEPE UNIV, 2015)
In this study, it has been examined that polyphonic solfege studies of cooperative learning based on approach Student Terms Achivement Divisions affect the success of the polyphonic solfege. In this research as post-test and pre-test control group with full trial model has been applied. The sample of the study in the academic year 2013-2014 consists of 22 people studying at Inonu University in Class 3. The implementation process covers a 10-week process. According to the method of straight expression have been applied to B the control group while improved programme based on cooperative learning approach have been applied to the experimental group. As a tool for data collection, reliability level .88 is calculated as Musical reading (solfege) performance test. Measurement and evaluation have been carried out by three specialists. After examining the level of normality for analysis of transactions related and unrelated samples t-tests were used. In addition, for calculating of the size of the impact, Cohens' d formula has been applied. According to the results of the research, it has been reached to the conclusion that applications to students based on cooperative learning approach has influenced on the success of the solfege polyphonic positively and highly.
Keywords: cooperative learning; solfege; polyphonic solfege; ABILITY; Education & Educational Research